2005
DOI: 10.1097/01.rhu.0000158542.43099.35
|View full text |Cite
|
Sign up to set email alerts
|

Audiovestibular Disorders in Patients With Ankylosing Spondylitis

Abstract: Middle-aged patients with AS had a significantly higher frequency of SNHL compared with controls. SNHL should be considered as a possible complication of AS as well as of RA and other autoimmune diseases. Possible toxic effect of nonsteroidal antiinflammatory drugs should also be considered in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
2
16
1
5
Order By: Relevance
“…Casellini et al [6] determined higher SNHL rates in 22 patients with AS than those in the control group. Alatas et al [4] reported the ratio of SNHL to be 28.6% in 28 patients with AS, whereas it was reported to be 4.3% in the control group.…”
Section: Discussionmentioning
confidence: 97%
“…Casellini et al [6] determined higher SNHL rates in 22 patients with AS than those in the control group. Alatas et al [4] reported the ratio of SNHL to be 28.6% in 28 patients with AS, whereas it was reported to be 4.3% in the control group.…”
Section: Discussionmentioning
confidence: 97%
“…It may be due to vasculitis, ossicular involvement, neuritis or ototoxicity of the drugs used for the treatment of rheumatologic diseases (18). Thus, hearing loss may be seen in conductive, sensorineural or in mixed pattern in secondary AIED (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(19)(20). Özcan et al suggested middle ear involvement for the reason of hearing loss in RA (18).…”
Section: Discussionmentioning
confidence: 99%
“…Bununla birlikte, otoakustik emisyon (OAE) gibi diğer testleri de içeren ve daha büyük örneklem büyüklüğüne sahip başka çalışmalara da ihtiyaç vardır. (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The inner ear pathologies caused by these disorders are commonly mild and slowly progressive whereas primary AIED is characterized by sudden onset, commonly bilateral, fluctuant and progressive sensorineural hearing loss (SNHL) with accompanying vertigo in some occasions.…”
Section: öZetunclassified
“…16 romatoid artritli 74 hastada tüm frekanslarda kontrol grubuna göre anlamlı işitme kaybı tespit etmişlerdir. Diğer bir çalışmada ankilozan spondilitli orta yaş grubu hastalarda kontrol grubuna göre yüksek frekanslarda işitme kaybı saptanmış ve sensörinöral işitme kaybının ankilozan spondilit ve diğer otoimmün hastalıkların sonucu olabileceği fikri öne sürülmüştür 18 . Alataş ve ark.…”
Section: Tablo 4 Yaş Ve Hastalık Süresi Etkisinden Arındırılmış Paşi̇unclassified